2016
DOI: 10.1002/jmri.25320
|View full text |Cite
|
Sign up to set email alerts
|

Neuroendocrine liver metastases: Value of apparent diffusion coefficient and enhancement ratios for characterization of histopathologic grade

Abstract: ADC is a promising marker for characterization of histopathologic grade of NETLM. These results should be confirmed in a prospective study. J. Magn. Reson. Imaging 2016;44:1432-1441.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 39 publications
1
12
0
Order By: Relevance
“…The use of dynamic enhanced CT has been described as being helpful in differentiating tumor pathologic grade in GEP-NENs. Some studies of pancreatic NENs have shown that well-differentiated tumors are more vascularized than poorly-differentiated tumors on enhanced CT (16)(17)(18). In our study, a higher degree of enhancement was found in LMs of well-differentiated GEP-NENs both in the hepatic arterial and portal venous phases compared to poorly-differentiated GEP-NENs.…”
Section: Discussionsupporting
confidence: 58%
“…The use of dynamic enhanced CT has been described as being helpful in differentiating tumor pathologic grade in GEP-NENs. Some studies of pancreatic NENs have shown that well-differentiated tumors are more vascularized than poorly-differentiated tumors on enhanced CT (16)(17)(18). In our study, a higher degree of enhancement was found in LMs of well-differentiated GEP-NENs both in the hepatic arterial and portal venous phases compared to poorly-differentiated GEP-NENs.…”
Section: Discussionsupporting
confidence: 58%
“…Several studies have shown that DWI is more sensitive for the detection of liver metastases than T2-weighted and multiphase gadolinium-enhanced MRI, especially for smaller lesions[ 72 - 74 ]. Besa et al [ 75 ] showed that the ADC of liver metastases from NEN weakly and significantly correlated negatively with tumor grade and Ki-67 and that the mean ADC and the minimum ADC values were significantly different between the three grades (1.6, 1.35 and 0.9 × 10 3 mm 2 /s and 0.84, 0.5 and 0.27 × 10 3 mm 2 /s for grades 1, 2 and 3, respectively). DWI is hence recommended in routine MRI abdomen protocol for the detection of liver metastases from NEN.…”
Section: Mrimentioning
confidence: 99%
“…Generally, hyper-enhancement has been considered as the common character of NETs [ 12 , 13 ]. The liver metastases of NETs tended to present similar enhancement features with their primary lesions [ 14 ].…”
Section: Discussionmentioning
confidence: 99%